Drosophila mind bomb2 is required for maintaining muscle integrity and survival. - Nguyen, H.T.; Voza, F.; Ezzeddine, N.; Frasch, M. (Journal of Cell Biology, 2007)
We report that the Drosophila mind bomb2 (mib2) gene is a novel regulator of muscle development. Unlike its paralogue, mib1, zygotic expression of mib2 is restricted to somatic and visceral muscle progenitors, and their respective differentiated musculatures. We demonstrate that in embryos that lack functional Mib2, muscle detachment is observed beginning in mid stage 15 and progresses rapidly, culminating in catastrophic degeneration and loss of most somatic muscles by stage 17. Notably, the degenerating muscles are positive for apoptosis markers, and inhibition of apoptosis in muscles prevents to a significant degree the muscle defects. Rescue experiments with Mib1 and Neuralized show further that these E3 ubiquitin ligases are not capable of ameliorating the muscle mutant phenotype of mib2. Our data suggest strongly that mib2 is involved in a novel Notch- and integrin-independent pathway that maintains the integrity of fully differentiated muscles and prevents their apoptotic degeneration.